Rancang Bangun Walker untuk Lansia dengan Fitur Adjustable Height: Analisis Kekuatan Struktur Menggunakan Simulasi Elemen Hingga - Batubara, Yongki; Radyantho, Kholiq Deliasgarin; Sujana, I Made Ivan Wiyarta Cakra; Margyanto, Ageng; Alfandy, Alev Putra; Attila, Muhammad Rayes; Suisman, Kelvin Febriano Wiranata (Jurnal Mekanik Terapan, 2025)
This study aims to design a walker for the elderly equipped with an adjustable height feature to improve user comfort and safety. The frame design was developed using CAD software and its structural strength was analyzed using the Finite Element Method (FEM). Simulations were carried out with static load variations ranging from 40 kg to 90 kg on aluminum alloy 6061-T4 material. The analyzed parameters include von Mises stress, equivalent strain, total deformation, and safety factor. The simulation results show a maximum von Mises stress of 28.99 MPa at a 90 kg load, which remains well below the material’s yield strength of 230 MPa, with a minimum safety factor of 7.849. These findings demonstrate that the walker design is safe to use within the tested load range. Future research is recommended to conduct dynamic structural testing and experimental validation of the physical prototype.